Kuzey Kıbrıs Türk Cumhuriyeti’nde Çalışan ve Çalışmayan Kadınların Duygusal Yeme Durumunun Vücut Ağırlığı ve Yaşam Doyumu Üzerine Etkileri - Uysal, Emel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study has been planned and conducted for the aim of evaluating the effects of emotional eating status on body weight and life satisfaction of women working and not working in Turkish Republic of Northern Cyprus (TRNC). It was applied on 384 female participants between 18-65 years who live in the region of Famagusta between December 2018 and May 2019. It’s implemented on the participants by Turkish Emotional Eating Scale, Life Satisfaction Scale, Personal Information Form, Information Form of Nutritional Habit, and Information Form of Anthropometric Measurement (body weight (kg), BMI (kg/m2), waist circumference (cm), hip circumference (cm)). According to the results of the study; it’s found a positive, strong and statistically significant correlation between the ratio measurements of the body weight (kg), BMI (kg/m2), waist circumference (cm), hip circumference (cm), and waist/hip ratio, and with Eating in Tension Cases, Eating for Coping with Negative Emotions, and Control Points Against Stimulus, which is a sub-dimension of the Emotional Eating Scale, of the female participants in the research who work or do not work. While determined a positive correlation between the measurements of the body weight (kg), BMI (kg/m2), waist circumference (cm), hip circumference (cm), and waist/hip ratio, and with the Self-Check Scores, which is a sub-dimension of the Emotional Eating Scale, of the female participants who do not work, there is no a statistically significant correlation between the female participants who work. There is no a statistically significant correlation between the measurements of the body weight (kg), BMI (kg/m2), waist circumference (cm), hip circumference (cm), and waist/hip ratio, and with the general scores of the Life Satisfaction Scale of female participants working and not working under the research. In addition, there is no a statistically significant correlation between the anthropometric measurements measurements of the body weight (kg), BMI (kg/m2), waist circumference (cm), hip circumference (cm), and waist/hip ratio, and with the general scores of the Life Satisfaction Scale of female participants working and not working under the research. There was a statistically significant difference between Eating in Tension Situations, Eating, Dealing with Stimulating Emotions, Self-Emotion Control and Self-Control Scores. Keywords: Women Working and Non-Working, Emotional Eating, Life Satisfaction

ÖZ: Bu çalışmada, KKTC’de yaşayan çalışan ve çalışmayan kadınların duygusal yeme durumlarının vücut ağırlığı ve yaşam doyumu üzerindeki etkilerinin değerlendirilmesi amacı ile planlanmış ve yürütülmüştür. Aralık 2018 - Mayıs 2019 tarihleri arasında, Gazimağusa bölgesinde yaşayan, 18-65 yaş arası 384 kadın katılımcı üzerinde yapılmıştır. Katılımcılara Türkçe Duygusal Yeme Ölçeği, Yaşam Doyumu Ölçeği, Kişisel Bilgi Formu, Beslenme Alışkanlığı Bilgi Formu ve Antropometrik Ölçüm Bilgi Formu (Vücut ağırlığı (kg), BKI (kg/m2), Bel çevresi (cm), Kalça çevresi (cm) ve Bel/Kalça oranı) uygulanmıştır. Araştırma sonuçlarına göre araştırmaya katılan çalışan ve çalışmayan kadın katılımcıların Duygusal Yeme Ölçeği alt boyutu olan Gerginlik Durumlarında Yeme, Olumsuz Duygularla Başa Çıkabilmek İçin Yeme ve Uyaran Karşısında Kontrol Puanları ile Vücut ağırlığı (kg), BKI (kg/m2), Bel çevresi (cm), Kalça çevresi (cm) ve Bel/Kalça oranı ölçümleri arasında pozitif yönlü, güçlü ve istatistiksel olarak anlamlı düzeyde korelasyon tespit edilmiştir. Araştırmaya katılan çalışmayan kadın katılımcıların Duygusal Yeme Ölçeği alt boyutu olan Kendini Kontrol Edebilme Puanları ile Vücut ağırlığı (kg), BKI (kg/m2), Bel çevresi (cm), Kalça çevresi (cm) ve Bel/Kalça oranı ölçümleri arasında pozitif yönlü korelasyon tespit edilirken, çalışan kadın katılımcılarda istatistiksel olarak anlamlı düzeyde korelasyon bulunmamaktadır. Araştırmaya katılan çalışan ve çalışmayan kadın katılımcıların Yaşam Doyum Ölçeği genel puanları ile Vücut ağırlığı (kg), BKI (kg/m2), Bel çevresi (cm), Kalça çevresi (cm) ve Bel/Kalça oranı ölçümleri arasında istatistiksel olarak anlamlı düzeyde korelasyon bulunmamaktadır. Araştırmaya katılan çalışan ve çalışmayan kadın katılımcıların antropometrik ölçümleri (vücut ağırlığı (kg), BKI (kg/m2), bel çevresi (cm), kalça çevresi (cm) ve bel/kalça oranı) ile Yaşam Doyumu Ölçeği genel puamları arasında istatistiksel olarak anlamlı düzeyle fark bulunmazken Duygusal Yeme Ölçeği alt boyutu olan Gerginlik Durumlarında Yeme, Olumsuz Duygularla Başa Çıkabilmek İçin Yeme, Uyaran Karşısında Kontrol ve Kendini Kontrol Edebilme Puanları arasında istatistiksel olarak fark vardır. Anahtar Kelimeler: Çalışan ve Çalışmayan Kadınlar, Duygusal Yeme, Yaşam Doyumu
Beslenme ve Diyetetik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Beslenme ve Diyetetik Bölümü, 2019. Tez Danışmanı: Yard. Doç. Dr. Sema Erge.
Keywords: Beslenme ve Diyetetik; Duygusal Beslenme, Depresyon, İştah--Cyprus, North; Emotional Nutrition; Depression; Çalışan ve Çalışmayan Kadınlar; Duygusal Yeme; Yaşam Doyumu; Women Working and Non-Working; Emotional Eating; Life Satisfaction